Preparation and Properties of Rice Resistant Octenyl Succiniate Anhydrate (OSA) Starch - Xue YANG; Shuwen WANG; Qingqing LIU; Hao YANG; Wenyue LI; Qingbin BAO (Shipin gongye ke-ji, 2022)
In order to explore new ways to prepare resistant starch and improve the utilization value of rice, especially broken rice resources, octenyl succiniate anhydrate (OSA) starch was prepared by water-phase using rice starch as raw material. Taking the degree of substitution DS and reaction efficiency RE as the investigation indicators, the effects of the reaction temperature, reaction pH, octenyl succiniate anhydride dropping time and starch concentration on DS and RE were studied. The OSA starch was subjected to wet heat treatment to explore the influence of the time of wet heat treatment on the content and physical and chemical properties of resistant starch, and to conduct an in vitro digestion test. The suitable process conditions were as follows: Reaction temperature was 40 ℃, reaction pH was 9.0, acid anhydride dripping time was 4 h, starch concentration was 30%, OSA starch DS=1.3915 and RE=78.2% obtained under these conditions. The OSA starch obtained under this condition was moist and heat treated for 18 h to prepare resistant starch octenyl succinate (resistant OSA starch), the resistant starch content increased from 25.2% to 42.2%, digestion experiments showed that the digestion and hydrolysis rate of resistant OSA starch in the simulated gastrointestinal tract was 58.8%。